Cancer survivors' experiences of using survivorship care plans: a systematic review of qualitative studies - Keesing, Sharon; McNamara, Beverley; Rosenwax, Lorna (Springer New York LLC, 2014)
Purpose: Cancer survivorship care plans (SCPs) are currently used in care settings to assist survivors during the transition from treatment to survivorship. In this paper, the experiences of cancer survivors are examined to provide their perspective of how survivorship care plans are used in practice. Methods: A systematic review and critical review of the qualitative literature regarding the experiences of cancer survivors using survivorship care plans was completed. Databases reviewed included CINAHL, AMED, Embase, MEDLINE, Informit, ProQuest, PsycINFO, ScienceDirect, Wiley Online Library, Scopus and Web of Science from 2000 to 2014.ResultsEleven qualitative studies were appraised for methodological quality and content. They revealed four key themes: stakeholders agreed that SCPs should be used as a key strategy for cancer survivors; there was a lack of consensus on the format, content and who should develop the SCP; cancer survivors do not consistently receive SCPs; and there was a lack of evidence to support the use of SCPs in practice. Conclusions: There is great potential for SCPs to assist cancer survivors and this is supported by the range of qualitative literature examined in this study. Further research is required to examine the many practical issues relating to the delivery of SCPs and how they may be used across a variety of care contexts as well as providing further evidence to support their use. Implications for Cancer Survivors: With further research, refinement and contributions made by survivors, health researchers and health care professionals, the survivorship care plan is proposed to be a useful and practical tool aimed at supporting the survivorship continuum of care.